The Relationship between Dissolved Solids Yield and the Presence of Snow cover in the Periglacial Basin of the Obruchev Glacier (Polar Urals) during the Ablation Season - Stachnik, Łukasz; Uzarowicz, Łukasz (Quaestiones Geographicae, 2011)
Hydrochemical investigations were carried out in the periglacial basin of Obruchev Glacier (Polar Urals, Russia) in order to provide a quantitative and qualitative comparison of dissolved solids yields during the ablation season with and without snow cover taking into account the mineral composition of rocks and deposits occurring in the studied area. The concentration of dissolved solids in the waters of the investigated basin is very low (about 7.0-8.9 μS cm-1). It is most of all due to harsh local climate conditions as well as the presence of minerals resistant to weathering in the parent material. Both factors contribute to the low rate of chemical weathering in the area. Results obtained indicate that a larger dissolved solids yield was transported during the period with snow cover (106 kg km-2 day-1, on average), than at the same time of the year but without snow cover (13 kg km-2 day-1, on average) indicating that melting snow is an important factor influencing the yield of dissolved solids in surface waters.